OS8 - 150 Encouraging Survival with Toca 511 and Toca FC Compared to External Lomustine Control. (18th October 2016) - Huang, T.T; Aghi, M.K; Chen, C.C; Elder, J.B; Kesari, S; Kalkanis, S; Kaptain, G; Landolfi, J; Mikkelsen, T; Portnow, J; Robbins, J.M; Ostertag, D; et al.
Abstract : Recurrent glioblastoma (GBM) has an unmet need for effective therapies. Toca 511 (vocimagene amiretrorepvec), a retroviral replicating vector with the transgene cytosine deaminase, selectively infects, persists and spreads in tumor. Subsequent oral administration of 5-fluorocytosine (Toca FC) produces 5-fluorouracil (5-FU) within infected cells. 5-FU kills cancer cells and myeloid derived suppressor cells, inducing robust antitumor immune responses in animal models. In 2 Phase 1 studies, Toca 511 was administered into the cavity wall after surgical resection (NCT01470794) or intratumoral injection by biopsy needle (NCT01156584). To provide context to the results observed, subjects were compared to an external lomustine treated control (Courtesy Denovo Biopharma; Wick 2010). Treatment with Toca 511/Toca FC from 2 Phase I studies showed significant improvement in OS HR equals to 0.48, p less than 0.001, with similar effect in the surgical resection (OS HR 0.45, p equals to 0.003) and intratumoral injection (OS HR 0.56, p equals to 0.060). Fewer related greater or equal to Grade 3 adverse events (AEs) were reported for Toca 511/Toca FC (2.5 percent) vs. lomustine (36.9 percent). There was a virtual absence of hematologic toxicity for Toca 511/Toca FC vs. lomustine (Grade greater or equal to 3 thrombocytopenia 23.8 percent). Discontinuations for AEs occurred in 0percent for Toca 511/Toca FC vs. 4.8 percent for lomustine. Toca 511 is surgically delivered and treatment-emergent AEs regardless of attribution included incision site pain (20 percent), procedural pain (12.5 percent), and wound infection (5 percent) vs. 0percent, 1.2 percent, 1.2 percent respectively for lomustine. Toca 511/Toca FC significantly improved survival and safety relative to lomustine. A Phase 2/3 trial has launched (NCT02414165).